THE EFFECTS OF SAMPLING ARTIFACTS ON COSMIC DUST FLUX ESTIMATES: A REEVALUATION OF NONVOLATILE TRACERS (OS, IR) - Peucker-Ehrenbrink B.; Ravizza G. (My University, 2000)
We reevaluate the effects of sampling artifacts on estimates of the flux of cosmic dust to Earth by modeling the population of extraterrestrial particles as a function of surface-area and time-interval sampled. Results from a Monte Carlo simulation for nonvolatile tracers such as Os and Ir indicate that samples corresponding to =<2.5 m2a adequately sample the incoming extraterrestrial particle population. This applies to nearly all extraterrestrial flux estimates based on Os isotope data for marine sediments. New and revised flux estimates based on Os isotopes in marine sediments constrain the flux of extraterrestrial matter to the sea floor to 30,000 +/- 15,000 metric tons per year, within error identical to estimates of the flux of extraterrestrial matter to the top of Earth's atmosphere. Care must be taken in the interpretation of iridium data for ice and snow samples because such samples are often too small to adequately sample the extraterrestrial particle population. The effects of systematic bias include large scatter in the data and underestimating the extraterrestrial matter flux.